Immobilization of Laccase in Alginate-Gelatin Mixed Gel and Decolorization of Synthetic Dyes - Mehdi Mogharabi; Nasser Nassiri-Koopaei; Maryam Bozorgi-Koushalshahi; Nastaran Nafissi-Varcheh; Ghodsieh Bagherzadeh; Mohammad Ali Faramarzi (Bioinorganic Chemistry and Applications)
Alginate-gelatin mixed gel was applied to immobilized laccase for decolorization of some synthetic dyes including crystal violet. The immobilization procedure was accomplished by adding alginate to a gelatin solution containing the enzyme and the subsequent dropwise addition of the mixture into a stirred CaCl2 solution. The obtained data showed that both immobilized and free enzymes acted optimally at 50°C for removal of crystal violet, but the entrapped enzyme showed higher thermal stability compared to the free enzyme. The immobilized enzyme represented optimum decolorization at pH 8. Reusability of the entrapped laccase was also studied and the results showed that ca. 85% activity was retained after five successive cycles. The best removal condition was applied for decolorization of seven other synthetic dyes. Results showed that the maximum and minimum dye removal was related to amido black 10B and eosin, respectively.